The Connection Between Dust Mite Number And Abiotic Factors In Boarding House Dust - Ainur Rofieq; Endrik Nurrohman; Wika Indriyanti (Postgraduate, University of Mataram, 2023)
Dust mites are insects that have a wide range and can cause a variety of allergy illnesses. The existence of mites in an environment can be affected by abiotic factors that espouse the growth of the mites. This research aims to analyze the connection between dust mite number and abiotic factors of boarding house dust. This research was descriptive. The research was conducted in Dau District, Malang Regency, using an analysis unit of student boarding houses and their residents (students) from 2018/2019 to 2019/2020. The research population consisted of student boarding houses that had been recognized as having disruptions due to exposure to house dust. The UMM Biology Laboratory was used to obtain research data. Inferential statistical tests with SPSS 21 software were employed as part of the analysis technique. The results of this research indicateÂ that room temperature, humidity, light intensity, wind speed, dry matter, ash content, protein content, crude fat, and crude fiber are abiotic factors that influence the TDR (House Dust Mites) population in boarding houses. Humidity is one of the abiotic factors that influence the existence of TDR among all the abiotic factors that influence the existence of TDR. The findings of this research can be utilized as a source of information for the general public, particularly students, to always pay attention to the cleanliness of their surroundings so that it does not become a medium for developing TDR and reducing the TDR population